Investment Analysis in The Millennial Era Using Capital Budgeting Approach - Desi Wulandari; Sri Trisnaningsih (International Journal of Economics Development Research (IJEDR), 2024)
This research aims to analyze the feasibility of investment in in vitro fertilization (IVF) services at PT. ASHA Indonesia. To achieve this goal, data collection techniques such as observation, interviews, and documentation were used. The data analysis techniques included cash flow, accounting rate of return, payback period, net present value, internal rate of return, present value, and net cash inflow. The results of the investment feasibility study, viewed from the Net Present Value (NPV), indicate that since the NPV is greater than the expected return, the investment in establishing IVF services at PT. ASHA Indonesia is deemed feasible. The analysis results for the Internal Rate of Return (IRR) show a rate of 33.48%, which is higher than 7%, indicating that the investment in IVF services at PT. ASHA Indonesia is feasible. The analysis results for the Average Rate of Return (ARR), which is greater than 7% (61.49% > 7%), and the Profitability Index (PI), which is greater than 1, also indicate that the investment in establishing IVF services at PT. ASHA Indonesia is feasible.